Advances in PET: the latest in instrumentation, technology, and clinical practice - Zhang, Jun; Knopp, Michael V. (Springer International Publishing, 2020)
PART I: Basics Science of Positron Emission Tomography -- Current status of PET Technology -- Current status and future directions of PET in clinical practice -- PART II: Solid State Digital PET Instrumentation, Technology and Clinical Practice -- Introduction to silicon photomultipliers for time-of-flight PET -- New Generation Silicon Photomultiplier-based Clinical PET/CT and PET/MR Systems -- Solid State Digital Photon Counting PET/CT -- Siemens Biograph Vision 600 -- PART III: Future Prospective of PET/CT Instrumentation and Technology -- Future Prospects of TOF PET Instrumentation and Technology.